Rythmes de mort - Dakhlia Jamil; Quemener Nelly; Castex Lucien (Temporalités)
This article analyses the specific temporalities of journalistic activity when covering the death of a celebrity. It sheds light on the different factors that determine the tempo of information given on the death of a well-known personality, and unravels the professional and media processes that sustain them. To do so, it presents quantitative and qualitative data resulting from the analysis of a corpus of 24.459 news headlines on dead celebrities spotted in the transmedia archive base OTMedia in 2012. Studying the circulation of news between radio, TV, the online press and the Web allows us to grasp the role of each media in the production of “death as event”. Two operations governing the informational pace of death are distinguished. The first concerns newsworthiness: gatekeeping means selecting the persons whose death deserves to be publicized. The second operation consists in the value-creation of the piece of news through a succession of different journalistic activities (time of news, time of homage, time of interrogations, “metareporting”). We hypothesize that obituaries are mostly fueled by controversies over life and death.